Extramammary Paget's disease of the perianal region: a 20‐year experience. Issue 3 (12th August 2014) - Rajendran, Saissan; Koh, Cherry E.; Solomon, Michael J.
Abstract: Background: To evaluate the results obtained from cases of perianal Paget's disease (PPD) and to provide a current perspective in the diagnostic evaluation and surgical management of this condition. Methods: A retrospective review of a single quaternary referral centre's experience with PPD from January 1994 to December 2013 was performed. Medical records were reviewed to collect data on demographics, preoperative investigations, complications, pathology and recurrence. A review of existing literature was also performed. Results: Five patients (four females, one male) with histologically confirmed PPD were identified. The median age of presentation was 72 (range 61 to 78). Three patients were recurrences following previous excisions and first presentations in two patients. Only one patient had an underlying diagnosis of cancer. The median time to diagnosis was 24 months. Four patients underwent wide local excision with skin graft and/or local flap reconstruction and one patient required an abdominoperineal excision for recurrence. Four patients had involved lateral margins despite wide local excision but follow‐up to date has only revealed one local recurrence. A review of available literature suggests that synchronous cancers can occur in up to 33% of patients and that a further 10% may be associated with metachronous cancers. Surveillance recommendations seem anecdotal and do not appear to be supported by available literature. Conclusion: PPD is a management challenge. Association with synchronous and metachronous carcinomas may not be as strong as initially thought. Surgery is the mainstay treatment with the need to balance between minimizing disease recurrence and functional sequelae from excessive tissue loss.